A good global investment for the United States: How investing in CGIAR makes America stronger, safer and more prosperous - Hill, Ruth Vargas; McNamara, Brian; Ringler, Claudia; Spielman, David J.; Thurlow, James; Berrospi, Maria Lucia; Chambers, Judith A.; Falck-Zepeda, José B.; Gilligan, Daniel O.; Glauber, Joseph W.; Hernandez, Manuel A.; Headey, Derek D.; et al. (International Food Policy Research Institute, 2025)
This report documents how CGIAR investments have delivered substantial economic, security, and diplomatic benefits for the U.S. that far exceed financial contributions. By driving agricultural innovation and providing evidence-based insights, CGIAR has boosted U.S. farm productivity, expanded export markets, and made food more affordable for American consumers. It has also helped prevent billions of dollars in potential damage from pests and diseases that threaten U.S. food security and farm livelihoods. CGIAR promotes American leadership in agricultural innovation by supplying the majority of the genetic materials used in U.S. crop breeding and acting as a critical research partner for U.S. businesses and universities. CGIAR also makes America safer and stronger through its work on predicting crises, protecting food security, and on improving livelihoods as an alternative to migration.